PEMBERKASAN ARSIP DINAMIS AKTIF DI SUBBAGIAN PERSURATAN DAN ARSIP AKTIF PADA ARSIP NASIONAL REPUBLIK INDONESIA (ANRI) - Mungky Hendriyani (ITB Swadharma, 2021)
The development of science and information technology in the current era of globalization has a big influence in all fields, especially information. This becomes very essential for an organization, both governmental and non-governmental institutions because every organization in its activities requires information to support the administrative process and implementation of management functions. Various kinds of documents and media have been created for the convenience of storing, searching, and disseminating information. Archives as an important source of information can support the process of administrative and bureaucratic activities. Filing of active archives within the National Archives of the Republic of Indonesia called ANRI uses a combined principle, namely the principle of centralization used in terms of establishing policies for active archive management systems, organizing, human resources, infrastructure, and facilities, as well as electronic archive management. The principle of decentralization is used in terms of structuring and physical storage of active archives located in the central file administration office of Echelon, Echelon II, and certain echelon III